Hubungan Tingkat Pengetahuan Dan Sikap Terhadap Penggunaan Obat Penyakit Jamur Kulit Di Desa Paku Alam - Putri, Ni Luh Nadia Santika; Syamsu, Erlina; Kurniawati, Darini (Jurnal Farmasi SYIFA, 2023)
Background: The development of knowledge and attitudes towards skin fungal infections has led to high public awareness to carry out self-medication for this disease, but it is necessary to pay attention to the accuracy in using drugs when carrying out self-medication. Lack of information and knowledge as well as attitudes in carrying out self-medication can have a negative impact on drug users such as ineffective treatment, doses that are too low or too high, emergence of resistance and unwanted effects of drugs. Objective: Knowing the relationship between the level of knowledge and attitudes towards the use of skin fungus disease drugs in Paku Alam Village. Methods: This research includes analytic observational with a cross sectional approach. The independent variable is the level of knowledge and attitude, while the dependent variable is the use of skin fungus medicine. Results: Analysis of the results using the Spearman rank correlation coefficient test on the relationship variable between attitudes and the use of skin fungus medicine obtained a p-value of 0.000 which means there is a significant relationship. Meanwhile, the relationship between knowledge and the use of skin fungus medicine resulted in a p-value of 0.000, which means that there is a significant relationship between the level of knowledge and the use of fungal disease drugs. Conclusion: There is a relationship between knowledge and attitude towards the use of skin fungal disease drugs with a significance value of 0.000. Keywords: attitude, knowledge, skin fungus, use